Effects of an energy‐restricted low‐carbohydrate, high unsaturated fat/low saturated fat diet versus a high‐carbohydrate, low‐fat diet in type 2 diabetes: A 2‐year randomized clinical trial. Issue 4 (20th December 2017) - Tay, Jeannie; Thompson, Campbell H.; Luscombe‐Marsh, Natalie D.; Wycherley, Thomas P.; Noakes, Manny; Buckley, Jonathan D.; Wittert, Gary A.; Yancy, William S.; Brinkworth, Grant D.
Abstract : Aim: To examine whether a low‐carbohydrate, high‐unsaturated/low‐saturated fat diet (LC) improves glycaemic control and cardiovascular disease (CVD) risk factors in overweight and obese patients with type 2 diabetes (T2D). Methods: A total of 115 adults with T2D (mean [SD]; BMI, 34.6 [4.3] kg/m 2 ; age, 58 [7] years; HbA1c, 7.3 [1.1]%) were randomized to 1 of 2 planned energy‐matched, hypocaloric diets combined with aerobic/resistance exercise (1 hour, 3 days/week) for 2 years: LC: 14% energy as carbohydrate, 28% as protein, 58% as fat (<10% saturated fat); or low‐fat, high‐carbohydrate, low‐glycaemic index diet (HC): 53% as CHO, 17% as protein, 30% as fat (<10% saturated fat). HbA1c, glycaemic variability (GV), anti‐glycaemic medication effect score (MES, calculated based on the potency and dosage of diabetes medication), weight, body composition, CVD and renal risk markers were assessed before and after intervention. Results: A total of 61 (LC = 33, HC = 28) participants completed the study (trial registration:http://www.anzctr.org.au/, ANZCTR No. ACTRN12612000369820). Reductions in weight (estimated marginal mean [95% CI]; LC, −6.8 [−8.8, −4.7], HC, −6.6 [−8.8, −4.5] kg), body fat (LC, −4.3 [−6.2, −2.4], HC, −4.6 [−6.6, −2.7] kg), blood pressure (LC, −2.0 [−5.9, 1.8]/ −1.2 [−3.6, 1.2], HC, −3.2 [−7.3, 0.9]/ −2.0 [−4.5, 0.5] mmHg), HbA1c (LC, −0.6 [−0.9, −0.3], HC, −0.9 [−1.2, −0.5] %) and fasting glucose (LC, 0.3 [−0.4, 1.0], HC, −0.4 [−1.1, 0.4] mmol/L) were similar between groups ( P ≥ 0.09). Compared to HC, the LC achieved greater reductions in diabetes medication use (MES; LC, −0.5 [−0.6, −0.3], HC, −0.2 [−0.4, −0.02] units; P = 0.03), GV (Continuous Overall Net Glycemic Action calculated every 1 hour (LC, −0.4 [−0.6, −0.3], HC, −0.1 [−0.1, 0.2] mmol/L; P = 0.001), and 4 hours (LC, −0.9 [−1.3, −0.6], HC, −0.2 [−0.6, 0.1] mmol/L; P = 0.02)); triglycerides (LC, −0.1 [−0.3, 0.2], HC, 0.1 [−0.2, 0.3] mmol/L; P = 0.001), and maintained HDL‐C levels (LC, 0.02 [−0.05, 0.1], HC, −0.1 [−0.1, 0.01] mmol/L; P = 0.004), but had similar changes in LDL‐C (LC, 0.2 [−0.1, 0.5], HC, 0.1 [−0.2, 0.4] mmol/L; P = 0.85), brachial artery flow mediated dilatation (LC, −0.5 [−1.5, 0.5], HC, −0.4 [−1.4, 0.7] %; P = 0.73), eGFR and albuminuria. Conclusions: Both diets achieved comparable weight loss and HbA1c reductions. The LC sustained greater reductions in diabetes medication requirements, and in improvements in diurnal blood glucose stability and blood lipid profile, with no adverse renal effects, suggesting greater optimization of T2D management.